Do Government Private Subsidies Crowd Out Entrepreneurship? - Islam, Asif (World Bank, Washington, DC, 2014)
Although several studies have found a negative relationship between government spending and entrepreneurship, much debate remains regarding the components of government spending responsible for this association. This paper contributes to the literature by specifically exploring the relationship between government private subsidies and entrepreneurship. By combining macroeconomic government spending data with individual level entrepreneurship data, the paper finds a negative association between the share of private subsidies and entrepreneurship. However, findings are less straightforward when the analysis delves deeper into the components of private subsidies and their association with different kinds of entrepreneurship.